Maternal mortality and caesarean delivery: A five year review - Huria, Anju; Mehra, Reeta; Gupta, Pratiksha; Goel, Bharti (Nepal Journal of Obstetrics and Gynaecology, 2010)
Aim: To find out maternal mortality related to caesarean delivery Methods: A review of maternal mortality in Government Medical College Hospital Chandigarh, India was conducted for the last five years. [2003 to 2007]. Results: Maternal mortality ratio was found to be 496.4 per 100,000 live births and of which 23.59% was causally or incidentally related to caesarean delivery. The caesarean delivery rates for the hospital was 29.08% in 2003 and a rising trend to 36.60% in 2007 was also noted. Conclusion: Caesarean remains a good option when rationally indicated; however the maternal and fetal conditions that indicate the operative delivery may be inherently related to mortality and morbidity. Key words: Maternal mortality; maternal mortality ratio; caesarean delivery DOI: 10.3126/njog.v4i1.3331 Nepal Journal of Obstetrics and Gynaecology June-July 2009; 4(1): 42-45